Front loading sputum microscopy – an alternative approach for diagnosis of pulmonary tuberculosis - Firdaus, Shehnaz (J Clin Tuberc Other Mycobact Dis, 2017)
INTRODUCTION: Until newer, rapid, economical tools are introduced for diagnosis of Pulmonary Tuberculosis in resource limited settings, optimization of sputum smear examination for increasing case detection remains of utmost priority. The aim of the study was to detect presumptive TB patients using Front Loading sputum microscopy and compare it with Standard method. METHODS: Three sputum specimens (Spot 1- on spot at the time of first visit, Spot 2- one hour after Spot 1 and early morning-next day early morning sample) from 552 TB suspect cases were collected. Zeihl Neelsen staining (spot 1, spot 2 and early morning respectively) and microscopy by Front Loading (spot 1, spot 2) and Standard method (spot 1, early morning) of sputum microscopy were done. RESULTS: Culture on LJ media being the gold standard, the sensitivity and specificity of the Front Loading and the Standard method of sputum microscopy were 68.65%, 94.43% and 70.14%, 93.6% respectively. The difference between two methods was not statistically significant. 91.1% patients gave preference for same day sampling process. CONCLUSION: The sensitivity and specificity of sputum microscopy using an early morning sample followed by another sputum one hour later from the same day appears not to be inferior to using two early morning samples on subsequent days. The Front Loading sputum microscopy can be implemented in DOTS clinic on the day of first visit of patients to health care center to increase compliance of patients with diagnostic procedure and decrease drop-outs.